ESG Investment (Environmental, Social, and Governance): A Solution in Achieving Maqashid Syariah - Dinary Rahmaningsih (Budapest International Research and Critics University, 2022)
ESG investment is often defined as an investment activity that considers the company's environmental, social and governance (“ESG”) factors in making investment decisions. The aim is to improve the long-term performance and competitiveness of the business that is the investment destination, as well as the long-term positive impact on society and the environment. Meanwhile, the Islamic finance industry aims to promote companies that are included in sectors or industries that provide added value to the real economy. Both the concept of ESG Investment and Islamic finance, both have similar values. Sharia investment is carried out based on sharia principles with the aim of achieving Maqasid Sharia (i.e. protecting the soul, religion, mind, lineage and property). Even in the concept of ESG investment, screening of certain business sectors is required. Thus, it has the potential to attract more interest from public companies as they seek to fulfill their social goals without compromising their business side operations. This paper offers insight into the ESG investment model from an Islamic perspective, particularly with regard to the concepts of maqasid sharia and maslahah mursalah. Further cooperation and education between regulators and professionals in the capital market industry is expected, leading to policies and initiatives such as promoting transparency and disclosure of investors, fund managers and companies in integrating ESG issues.